Análise da frequência de polimorfismos genéticos de il6 e il1rn nas infecções de pacientes submetidos à fixação de fraturas faciais - Mello, Manoel de Jesus Rodrigues (2018)
Facial fractures are one of the most common types of trauma affecting the skeletal system and may cause not only aesthetic problems but also functional problems. Well-done reduction, stabilization and fixation of the fractured bone segments allow a satisfactory consolidation, making possible the maintenance of the bone structure. Epidemiological aspects are strongly associated with social changes in people's lives, as well as poor education, lack of public controls, impaired streets and roads infrastructure, increased social motorization, negligence in traffic, use of illicit drugs, increased physical aggression in public road and changes in sports aggressiveness. The objective of this study is to analyze the epidemiological and microbilogical profile of the patients who had this type of fracture, evaluating whether a genetic component may be associated and that this process may be modulated by polymorphisms in genes that encode inflammatory cascade cytokines. Hence, relating the association between the IL6 and IL1 RN polymorphisms and infections in patients from Brazilian Northeast who underwent surgical treatment with fixation of titanium miniplates, at the Dr. José Frota Institute Hospital. Therefore, 5 ml of blood was collected from 96 patients. The presence of polymorphisms was determined by DNA extraction, by PCR and PCR-RFLP. As results, 96 patients were evaluated in this study, of which 78 (81.3%) were male, and 18 (18.8%) were female. Regarding to the IL6 gene, only 2 (2.1%) patients presented polymorphism (CC), 29 (30.9%) were heterozygous (GC), and 63 (67.0%) presented the wild gene (GG). Regarding to the IL1 RN gene, only 8 (8.5%) patients presented polymorphism (CC), 44 (46.8%) were heterozygous (CL), and 42 (44.7%) presented the wild gene (LL). Infection of the surgery was observed in 15 (15.6%) patients, and infection associated with loss of fixation was observed in only 4 (4.2%). No patient presented the polymorphism of the two genes, and there was no statistically significant difference between the prevalence of IL6 and IL1 RN gene polymorphism (p = 1,000). Thus, it can be concluded that there is a low loss of fixation of facial fractures, even in patients who presented postoperative infection, however, IL6 gene polymorphism may be considered a risk factor for the development of infection, regardless of gender and polymorphism of the IL1 RN gene.